2016
DOI: 10.3847/0004-637x/827/1/58
|View full text |Cite
|
Sign up to set email alerts
|

OBSCURED AGNs IN BULGELESS HOSTS DISCOVERED BY WISE: THE CASE STUDY OF SDSS J1224+5555

Abstract: There is mounting evidence that supermassive black holes form and grow in bulgeless galaxies. However, a robust determination of the fraction of AGNs in bulgeless galaxies, an important constraint to models of supermassive black hole seed formation and merger-free models of AGN fueling, is unknown, since optical studies have been shown to be incomplete for low mass AGNs. In a recent study using the Wide-field Infrared Survey Explorer, we discovered hundreds of bulgeless galaxies that display mid-infrared signa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 167 publications
0
7
0
Order By: Relevance
“…The isolation of the system, however, implies that whatever morphological changes Was 49b underwent happened during the beginning of its encounter with Was 49a, and so it has not been severely tidally stripped (unlike, for example, the SMBH-hosting ultracompact dwarf galaxy M60-UCD1; Seth et al 2014), suggesting that the SMBH was intrinsically overmassive or that perhaps the black hole's growth during the early phase of the merger happened well before the buildup of its host galaxy (e.g., Medling et al 2015; see also the Discussion in van Loon & Sansom 2015). If Was 49b was originally a late-type/dwarf galaxy, its SMBH is a factor of 10 2 -10 4 as massive as other black holes found in this galaxy type, which are typically between 10 4 and 10 6   M (e.g., Filippenko & Ho 2003;Barth et al 2004;Izotov & Thuan 2008;Shields et al 2008;Reines et al 2011Reines et al , 2013Dong et al 2012;Secrest et al 2012Secrest et al , 2013Secrest et al , 2015Maksym et al 2014;Moran et al 2014;Baldassare et al 2015Baldassare et al , 2016Mezcua et al 2016;Satyapal et al 2016), potentially giving new insight into how SMBHs form and grow in isolated systems. For example, recent work has suggested that black hole mass growth at higher redshifts precedes bulge growth (e.g., Zhang et al 2012), while other work has found no such effect (e.g., Schulze & Wisotzki 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of the system, however, implies that whatever morphological changes Was 49b underwent happened during the beginning of its encounter with Was 49a, and so it has not been severely tidally stripped (unlike, for example, the SMBH-hosting ultracompact dwarf galaxy M60-UCD1; Seth et al 2014), suggesting that the SMBH was intrinsically overmassive or that perhaps the black hole's growth during the early phase of the merger happened well before the buildup of its host galaxy (e.g., Medling et al 2015; see also the Discussion in van Loon & Sansom 2015). If Was 49b was originally a late-type/dwarf galaxy, its SMBH is a factor of 10 2 -10 4 as massive as other black holes found in this galaxy type, which are typically between 10 4 and 10 6   M (e.g., Filippenko & Ho 2003;Barth et al 2004;Izotov & Thuan 2008;Shields et al 2008;Reines et al 2011Reines et al , 2013Dong et al 2012;Secrest et al 2012Secrest et al , 2013Secrest et al , 2015Maksym et al 2014;Moran et al 2014;Baldassare et al 2015Baldassare et al , 2016Mezcua et al 2016;Satyapal et al 2016), potentially giving new insight into how SMBHs form and grow in isolated systems. For example, recent work has suggested that black hole mass growth at higher redshifts precedes bulge growth (e.g., Zhang et al 2012), while other work has found no such effect (e.g., Schulze & Wisotzki 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 7, we plot the CO EWs for three different M11 instantaneous starburst models corresponding to Kroupa, Chabrier, and Salpeter initial mass functions (IMFs), as a function of time (see Satyapal et al (2016) for details). The horizontal dashed lines indicate the observed EWs for the targets in our sample.…”
Section: The Contribution From X-ray Binariesmentioning
confidence: 99%
“…Following the procedure described in Satyapal et al (2016), we compared the observed EWs of the CO bandhead with the Maraston & Strömbäck (2011; hereafter M11) set of intermediate-high resolution stellar population models. In Figure 7, we plot the CO EWs for three different M11 instantaneous starburst models corresponding to Kroupa, Chabrier, and Salpeter initial mass functions (IMFs), as a function of time (see Satyapal et al (2016) for details).…”
Section: The Contribution From X-ray Binariesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AGN identification methods based on red mid-IR colors become more ambiguous for low-luminosity AGNs (e.g., Hainline et al 2016). In particular, recent studies have found that the vast majority of low-mass galaxies with red mid-IR color do not show any sign of optical emission lines powered by AGNs (Satyapal et al 2014(Satyapal et al , 2016Sartori et al 2015;Secrest et al 2015). Several studies have also demonstrated that young, compact starbursts in dwarf galaxies can have mid-IR colors mimicking those of luminous AGNs (e.g., Griffith et al 2011;Izotov et al 2014;Hainline et al 2016).…”
Section: Mid-ir Colorsmentioning
confidence: 99%